IDENTIFIKASI GUA KUMAPO DI DESA LELEKA KECAMATAN WOLASI KABUPATEN KABUPATEN KONAWE SELATAN - Fendi Pradana; sitti kasmiati (SANGIA: Jurnal Penelitian Arkeologi, 2017)
The Southeast Sulawesi region is one of the areas that also still holds many issues regarding archaeological remains, especially archeological remains scattered in prehistoric caves. one of thelocations of prehistoric caves that can still be observed archeological remains in the area of SouthKonawe District, Wolasi Subdistrict, Leleka Village, with the type of archaeological remains one ofwhich is the Graveyard. and how cave functions are based on their archaeological findings. Thepurpose of this study was to find out the archaeological remains found in the Lapeka Village kumapocave and to find out the function of the kumapo cave based on its archaeological findings. This studyfocused on the findings of artifacts and non-artifacts found on the Leleka Village kumapo cave site. Thetype of research used is qualitative research using an inductive approach. The results showed that thearcheological findings found in the Lapeka Village kumapo cave were in the form of burial containers (duni) with 3 pieces, 7 pieces of broken fragments, and 3 beads. Another finding is in the form of nonartefactual findings, namely human bones.